Kalibrator Infant Warmer Berbasis Arduino Uno Dilengkapi dengan Penyimpanan Data - Bayu Wahyudi; Diah Rahayu Ningtias; Ardian Widyastuti (Elektrika, 2023)
Calibration is an activity to determine the conventional correctness of the designation value of measuring instruments and measuring materials by comparing them with traceable measuring standards to national standards for units of measure and/or international ones. One example of a tool used for calibration is the Infant Warmer Calibrator. The purpose of this research is to produce a tool that can be used to calibrate and analyze temperature and humidity data on infrant warmers. This tool uses five LM35 type temperature sensors with Arduino as the main controller for this tool, and is also equipped with a DHT11 type humidity sensor, and is also equipped with an SD Card as storage. From the results of the study, different results were obtained with the largest error difference of 1.85% at a test point of 35°C and the smallest error presentation was 1.3% at a test point of 34°C and the tool was functioning properly.